A stolen life : a memoir - Dugard, Jaycee Lee, 1980- (New York : Simon & Schuster, 2011)
The memoir of Jaycee Dugard who was kidnapped on June 10, 1991, when she was 11 years old, and was missing for over 18 years before her reappearance in 2009.
Keywords: Dugard, Jaycee Lee, -- 1980- -- Kidnapping, 1991.; Kidnapping victims -- California -- Biography; Kidnapping -- California; Sexually abused children -- California -- Biography; Autobiographies